Efficacy of intranasal dexmedetomidine-esketamine sedation for pediatric acceptance of facemask: single-center, double-blind, randomized, controlled trial - Kan Zhang; Guangxuan Zhang; Yanmei Zhang; Jingjing Wang; Jie Bai; Jijian Zheng; Yujuan Tao (BMC Anesthesiology)
Abstract Objective We compare the efficacy of intranasal dexmedetomidine (DEX) and DEX-esketamine sedation on pediatric acceptance of face mask. Methods This single-center double-blind randomized controlled study was conducted at a tertiary hospital affiliated with Shanghai Jiao Tong University. Ninety children aged 1 year to 6 years old and scheduled for elective surgery were randomly allocated in a 1:1 ratio into receiving DEX alone (n = 45) and DEX-esketamine (n = 45). DEX and esketamine were used intranasally at doses of 2 µg/kg and 2.0 mg/kg respectively. Children were assessed by an attending anesthesiologist with modified observer’s assessment of alertness and sedation (MOAA/S), pediatric separation anxiety scale (PSAS) and mask acceptance scale (MAS). Perioperative adverse events (bradycardia, hypotension, hypoxia, emergence delirium etc.) were recorded. Results Of 95 patients enrolled, 90 completed the study. The proportion of children who accepted facemask was significantly higher in the DEX-esketamine group compared to the DEX group (86.7% (39/45) vs. 62.2% (28/45), p = 0.008). Within 30 min after intranasal administration of agents, PSAS scores were similar between the two groups. Children in the DEX group were easily aroused when repositioned from the transferring bed to the operation table. In contrast, those in the DEX-esketamine group maintained a stable level of sedation (MOAA/S scores, median [25th– 75th interquartile range], 1 [1, 1] for DEX-esketamine vs. 2 [1, 4] for DEX, p < 0.001). Furthermore, subgroup analysis found that DEX-esketamine provided better facemask acceptance in children with high anxiety (PSAS ≥ 3). There were no significant differences in perioperative heart rate, noninvasive blood pressure and percutaneous arterial oxygen saturation between the two groups. Postoperative extubation time and perioperative adverse events were also comparable between the groups (all p > 0.05). Conclusions For preoperative sedation, combination of DEX with esketamine improved mask acceptance than dexmedetomidine alone, likely due to its superior anxiolytic effect in children with high anxiety. Trial registration This study was registered in the Chinese Clinical Trial Register (registration no. ChiCTR2400087873, registration date on 6/8/2024).